2009
DOI: 10.9775/kvfd.2011.5426
|View full text |Cite
|
Sign up to set email alerts
|

İran’ın Orumieh Şehri’nden Toplanan Ballarda Metal Düzeylerinin Belirlenmesi

Abstract: In this study the concentrations of metals in 89 different honey samples were collected, from four different areas of Orumieh City, in Iran from September of 2009 were investigated. Most of the samples were obtained from beekeepers located at a distance of 10 km from the roadside, to their accommodation. Pb, Co, Cr, Fe, Mn, Zn, As and Ni were detected in all of the honey samples. The contents of metals in honey samples were found to be in the range of 0.04±0.1 ppm, 0.001±0.002 ppm, 7.09±9.4 ppm, 0.6±0.9 ppm 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Only in one area Pb level was detected highly (1.390 mg kg), this linked to the petroleum extraction-related and touristic activities, high movement of vehicles, especially in the spring-summer period. In Saghaei et al [15] study, metal levels detected from the honey collected from four different areas of Orumieh City, in Iran. The results indicated that Zn had highest concentration followed by Cr, Fe, Mn, Pb, Ni, Co and As.…”
Section: Discussionmentioning
confidence: 99%
“…Only in one area Pb level was detected highly (1.390 mg kg), this linked to the petroleum extraction-related and touristic activities, high movement of vehicles, especially in the spring-summer period. In Saghaei et al [15] study, metal levels detected from the honey collected from four different areas of Orumieh City, in Iran. The results indicated that Zn had highest concentration followed by Cr, Fe, Mn, Pb, Ni, Co and As.…”
Section: Discussionmentioning
confidence: 99%
“…Despite considerable progress in the development of physical and chemical methods of bee products analysis, for instance, spectroscopic [1,2,[6][7][8][9][10][11][12][13] and chromatographic ones [14], such analyses require complicated and valuable equipment, and as a result are expensive.…”
Section: Introductionmentioning
confidence: 99%
“…For full destroying of the organic matrix of honey samples dry and hydro ashing is usually used. It is performed mostly by acids: nitric acid [1,8], chloric [11], mixture of nitric and chloric acids [8], mixture of nitric and sulfate acids [9], as well as by nitric acid and hydrogen peroxide [2,7,14] and mixture of nitric acid and magnesium acetate [10,13]. Besides traditional samples heating at their mineralization, a more advanced method is using devices with microwave heating for hydro ashing under pressure, which is actually described in works [2,7].…”
Section: Introductionmentioning
confidence: 99%